Studies on fibre quality parameters of inovulo cultured interspecific triple cross of cotton - Hingane, Anupama; Mehetre, S.S. (Annals of Agricultural Research, 2014)
Currently, spinning machinery used by the textile processing industry sets the standards for fibre quality and these are mostly based on the physical properties of fibre, especially strength. Therefore, an important breeding objective has been to introduce fibre strength genes from other Gossypium species or strains while maintaining the cotton fibre yield. Amongst wild Gossypium L. species, the African Gossypium anomalum produces cotton with good fibre strength and fineness. In this investigation, efforts were made to introgress superior fibre quality parameters from wild G. anomalum and G. barbadense into G.arboreum cotton and obtained hybrid between colchicide (G. arboreum x G. anomalum) x G. barbandense. In the present study F3 and F4 generation of inovulo cultured interspecific triple cross were evaluated to determine desirable fibre quality parameters for high spinning potential of the textile mills. On the basis of fibre analysis, seven F3 segregants viz, 10aab/3, 9T/7, 9T/1, 30A/3, 4T/5, 73/9, 73/6 showed highest performance for the entire fibre quality attribute. Similarly 56/6-2, 4T/5-13, 9T/3-20, 13W/9-2, 45/3-18 and 9aab/8-5 F4 plants had desirable fibre properties. Identification of these plants will enable to undergo the selection pressure for such type of plants in succeeding generation to enhance the fibre quality parameters.